Reformulating Administrative Sanctions for Regional Heads and Legislative Members in Delays of Regional Budget Approval in Indonesia - Sartono, S.; Suhartono, Slamet; Fahmi, F. (Journal of Ecohumanism, 2024)
Delays in approving regional budget draft regulations (Perda R-APBD) remain a critical issue in Indonesia, often leading to stagnation in regional development and governance. This study explores the reformulation of administrative sanctions for regional heads and members of the Regional People’s Representative Council (DPRD) as a legal response to persistent delays. Utilizing a doctrinal legal research method, this paper analyzes inconsistencies and inefficiencies in the current regulatory framework, specifically under Articles 312 and 313 of Law No. 23 of 2014 on Regional Government. The findings highlight normative contradictions and propose an integrated legal mechanism to ensure accountability and collaborative governance. This reform is expected to foster better budgetary discipline and contribute to sustainable regional development.